Nrf2 Expressions Correlate with WHO Grades in Gliomas and Meningiomas - Tsai, Wen-Chiuan (Int J Mol Sci, 2016)
Background: Nuclear factor erythroid 2-related factor 2 (NFE2L2, also known as Nrf2) is associated with cellular progression and chemotherapeutic resistance in some human cancers. We tested the relationship between Nrf2 expression and survival of patients with primary brain tumors (PBTs). Methods: In order to realize Nrf2 protein expression in gliomas, Western blot analysis was performed in normal brain tissue and U87MG, LN229, GBM8401 and U118MG glioma cell lines protein lysates. Then, U87MG, LN229, and GBM8401 mRNA were applied to performed quantitative RT-PCR for detect Nrf2 gene expression in glioma cell lines. At last, immunohistochemical analysis was used to determine the expression of Nrf2 in samples from 178 PBTs and 10 non-neoplastic brain tissues. Results: In these included in vitro studies, both Nrf2 protein and mRNA expression in all human glioma cell lines were higher than normal brain tissue. Similarly, on the viewpoint of immunohistochemistry, Nrf2 expression in gliomas were positively correlated with World Health Organization (WHO) grades. Additionally, compared with the expression of Nrf2 in non-neoplastic brain tissue, expression in meningiomas was of a stronger intensity and was present in a higher percentage of cells. Furthermore, scores were significantly higher in WHO grade II than in WHO grade I meningiomas. Finally, overall survival tended to be shorter in patients whose PBTs had higher expression of Nrf2, although the correlation was not statistically significant. Conclusions: Nrf2 overexpression positively correlated with WHO grade in gliomas and meningiomas. On the other hand, Nrf2 immunohistochemical stain could help pathologists to differentiate atypical meningiomas from benign tumors. Therefore, Nrf2 expression may be a useful biomarker to predict WHO grade and cellular behavior of PBTs.